2007
DOI: 10.1152/ajplung.00061.2007
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cGMP-dependent protein kinase-mediated vasodilation by hypoxia-induced reactive species in ovine fetal pulmonary veins

Abstract: Regulation of cGMP-dependent protein kinase-mediated vasodilation by hypoxia-induced reactive species in ovine fetal pulmonary veins. Am J Physiol Lung Cell Mol Physiol 293: L1012-L1020, 2007. First published July 6, 2007 doi:10.1152/ajplung.00061.2007.-We previously reported that hypoxia attenuates cGMP-dependent protein kinase (PKG)-mediated relaxation in pulmonary vessels (Am J Physiol Lung Cell Mol Physiol 279: L611-L618, 2003). To determine whether hypoxia-induced reactive oxygen and nitrogen species (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
54
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 65 publications
11
54
2
Order By: Relevance
“…These Cav1 null cells may experience mitochondria dysfunction, leading to nitrative stress as evident by peroxynitrite formation. In contrast to the observation in Cav1 -/-mice, hypoxia-induced PKG nitration is eNOSindependent but iNOS-dependent [45]. Thus, it is possible that both tissue hypoxia and inflammation will result in increased nitrative stress and PKG nitration through iNOS.…”
Section: Pkg Nitration-mediated Impairment Of Pkg Activity May Be a Ccontrasting
confidence: 70%
See 2 more Smart Citations
“…These Cav1 null cells may experience mitochondria dysfunction, leading to nitrative stress as evident by peroxynitrite formation. In contrast to the observation in Cav1 -/-mice, hypoxia-induced PKG nitration is eNOSindependent but iNOS-dependent [45]. Thus, it is possible that both tissue hypoxia and inflammation will result in increased nitrative stress and PKG nitration through iNOS.…”
Section: Pkg Nitration-mediated Impairment Of Pkg Activity May Be a Ccontrasting
confidence: 70%
“…It has been shown that hypoxia impairs PKG activity and PKG-mediated relaxation in ovine fetal intrapulmonary veins through both downregulation of PKG expression and tyrosine nitration of PKG [45]. Other studies also show decreased PKG activity and resultant attenuated vasodilatory responses to exogenous NO and cGMP in rats following chronic hypoxia [44].…”
Section: Pkg Nitration-mediated Impairment Of Pkg Activity May Be a Cmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the nitration and subsequent attenuation of PKG activity in the right ventricle appears to be responsible for the deterioration of right ventricle function in a mouse model of pulmonary hypertensive induced by chronic hypoxia (43). However, the increase in protein nitration associated with hypoxia reduces PKG activity through changes at the transcriptional and post-translational levels (2). The clinical relevance of PKG nitration has also been shown by the observation that patients with idiopathic pulmonary arterial hypertension have increased PKG nitration in their lungs with no noticeable alteration in PKG protein levels (3).…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro and in vivo studies have demonstrated that the nitration of cGMP-dependent protein kinase G-1␣ (PKG-1␣) 4 is a key post-translational event responsible for the impaired PKG activity in the lungs of acute and chronic pulmonary hypertensive lambs (1), mice with hypoxia-induced pulmonary hypertension (2), and humans with idiopathic pulmonary arterial hypertension (3). However, the tyrosine residues susceptible to this nitration event and the mechanism(s) by which nitration inhibit PKG-1␣ activity are unclear and were the focus of this study.…”
mentioning
confidence: 99%